Architecture of porous CoS1.097-C composite nanowire for efficient oxygen reduction reaction. (5th February 2019) - Jinyu, Zhang; Liping, Sun; Fanhao, Kong; Lihua, Huo; Hui, Zhao
Abstract: Design and preparation of efficient and low cost electrocatalysts for the oxygen reduction reaction (ORR) is vitally important for the commercialization of alkaline direct methanol fuel cell (ADMFC). Herein, porous CoS1.097 -C composite nanowire is prepared by one-step in-situ pyrolyzing Co-nitrilotriacetic acid (Co-NTA) precursor in Ar atmosphere with adding S powder. The obtained CoS1.097 -C composite nanowire gathered by carbon encapsulated CoS1.097 nanoparticles are further analyzed by FT-IR, XRD, SEM, TEM, Raman, BET and XPS. The optimized CoS1.097 -C composite nanowire catalyst shows the onset potential of 0.90 V and half-wave potential of 0.79 V with the acquired tafel slope of 57.7 dec −1 for ORR in 0.1 M KOH. Further studies indicate that the effective four-electron pathway contributes to excellent ORR activity. Moreover, the CoS1.097 -C composite nanowire catalyst exhibits good durability and methanol tolerance over the commercial Pt/C. This work provides a general strategy for developing carbon-based transition metal sulfide nanocomposite as cathode in ADMFC. Graphical abstract: Highlights: One step in-situ annealing Co-NTA precursor is used to prepared porous CoS1.097 -C nanowire. Porous CoS1.097 -C nanowire is studied as ORR catalyst with commendable performance. Compared with commercial Pt/C, porous CoS1.097 -C nanowire has excellent methanol tolerance.